Applied Literature: A Proposal for Delimiting the Concept and Classifying its Documented Uses - Clavijo, Daniel; Lara-Viana, Matilda; Pino-Posada, Juan Pablo (Íkala, Revista de Lenguaje y Cultura, 2025)
Most efforts to conceptualize the notion of applied literature and to identify the uses of literary discourse have been focused on the textual level, overlooking potential literary practices in extratextual realities. Moreover, there is a lack of precision in these approaches about the functioning of literary devices and resources in their different application scenarios. To fill this gap, this article proposes a definition of applied literature that transcends the intertextual sphere, to account for its scope in different areas of social activity, and presents a classification of the ways in which literary discourse is used and the scenarios in which it intervenes, based on the description of a series of documented processes. The schema presented allows to synthesize the experiences in which literature has been used—at a rhetorical, poetic or hermeneutic level—in collective scenarios and identifies its possibilities for thematic positioning or broadening perspectives in pedagogical, therapeutic or political action spheres.